Experimental modal identification and fem updating of a seven story isolated educational building - Reategui, Rony (2019)
The construction of isolated structures is increasing in recent decades in seismic countries. In Peru, the national regulation indicates that important buildings such as hospitals located in areas of high seismic risk must incorporate isolation systems to reduce structural and nonstructural loss. These systems protect the main structure from the effects of a seismic event by separating its base from the earth movement and by reducing the relative displacements and accelerations between adjacent stories. In the structural design process of buildings and seismic protection systems, having numerical models that properly represent the real behavior of the buildings is of high importance. In this context, experimental modal tests represents an attractive cost-effective non-destructive tool to obtain an accurate characterization of the experimental structural response. This paper presents the experimental tests carried out in a base-isolated educational building built in 2014 that has seven stories and three basements with a total built area of around 7500 m2. Data acquisition was accomplished with autonomous units (acquisition system and transducers incorporated in a single unit) whose versatility allowed measuring a significant number of degrees of freedom in a limited amount of time. The dynamic properties experimentally identified were used to calibrate the finite element model of the building. The results showed that the design model approximates correctly to the experimentally identified ambient vibration response when considering rigid supporting conditions as well as the interaction of partitioning elements such as walls and parapets.